Tinjauan Kriminologis Terhadap (Residive) Pengulangan Pencurian di Kelurahan Fatululi, Kecamatan Oebobo, Kota Kupang. - Hutama, Galih Sunarya Putra; Leo, Rudepel Petrus; Kian, Darius Antonius (Law Faculty, Nusa Cendana University, 2023)
Currently, various types of crimes can occur. One type of crime that often occurs and is very disturbing in the community is the act of theft of gold necklace jambret occurs in big cities, including the city of Kupang. The crime of stealing a gold necklace jambret harms many people. Because the price is unbelievably cheap. People use gold usually for investment or storage of valuables in their old age when they no longer have savings for daily life needs. The locations that are usually targeted by burglars are very diverse, in residential areas, parking lots, public or special parking lots in schools, campuses, government agency offices, crowded markets, etc. From the description above, the main problem is as follows: (1) What is the factor that causes the repetition of the crime of theft (recidivism) in Fatululi Village, Oebobo District, Kupang City? (2) What are the efforts to combat the repetition of the crime of theft (recidivism) in Fatululi Village, Oebobo District, Kupang City? The purpose of this research is to find out the criminological review of (recidivism) theft in Fatululi Village, Oebobo District, Kupang City. that is: Usually the cause of the occurrence (Recidivism) is a factor that is related to each other such as education, environment, economy, and low criminal sanctions. (2) Efforts to Combat Repeated Theft Crimes (Recidivism) in Fatululi Village, Oebobo Subdistrict, Kupang City are: (a) Preemptive efforts are to prevent crimes from happening for the first time. (b) Preventive efforts. In this effort, by doing legal counseling and giving lessons about legal arrangements to families and the community. (c) Repressive efforts. In this effort, legal actions are carried out in the form of arrests and detentions carried out by law enforcers such as the police, prosecutors and courts.